Association between glial fibrillary acidic protein, glial-derived neurotrophic factor, and fatty acid-binding protein-2 at birth in the incidence of necrotizing enterocolitis in preterm infants - Angelika, Dina; Etika, Risa; Fitriah, Munawaroh; Kusumawardani, Naomi Nathania; Vita, Angelica Diana; Irawan, Roedi; Liem, Kian Djien; Ugrasena, I Dewa Gede (Frontiers in Pediatrics, 2022)
Background: This study aimed to analyze the relationship between glial fibrillary acidic protein (GFAP), glial-derived neurotrophic factor (GDNF), and fatty acid-binding protein-2 (FABP-2) in preterm infants on the incidence of NEC. Methods: Preterm infants with a birth weight < 1500 g and gestational age < 34 weeks were included in this study. Biomarker examination was performed using the umbilical vein blood at birth (first sample). Biomarker examination was repeated if the infant developed symptoms of NEC using peripheral vein blood (second sample). Infants were observed for 14 days. If NEC did not exist, a biomarker examination was performed at 14 days. Results: This study included 30 preterm infants, nine infants experienced NEC. The median values of GFAP, GDNF, and FABP-2 in the group with NEC were higher than those in the group without NEC in both the first and second samples. In infants with NEC, the median values of GFAP, GDNF, and FABP-2 in the second sample were higher than those in the first sample. Logistic regression demonstrated that GFAP at birth (Odds Ratio [OR] =15.629, 95% Confidence Interval [CI] = 1.697-143.906, P=0.015) and FABP-2 levels at birth (OR = 1.008, 95% CI = 1.001-1.015, P=0.033) were significantly associated with an increased risk of NEC. Conclusion: Increased GFAP, GDNF, and FABP-2 at birth are associated with NEC occurrence within two weeks of birth. These findings suggest that early-onset NEC is associated with intestinal injury that occurs during the perinatal or even prenatal period.